2017
DOI: 10.3390/nano7050093
|View full text |Cite
|
Sign up to set email alerts
|

Probing Temperature- and pH-Dependent Binding between Quantum Dots and Bovine Serum Albumin by Fluorescence Correlation Spectroscopy

Abstract: Luminescent quantum dots (QDs) with unique optical properties have potential applications in bio-imaging. The interaction between QDs and bio-molecules is important to the biological effect of QDs in vivo. In this paper, we have employed fluorescence correlation spectroscopy (FCS) to probe the temperature- and pH-dependent interactions between CdSe QDs with carboxyl (QDs-COOH) and bovine serum albumin (BSA) in buffer solutions. The results have shown that microscopic dissociation constant K′D is in the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Reports have shown enthalpy-driven binding of bovine serum albumin (BSA) to QDs, wherein at high temperature the BSA binding was lowered. 51 The normal body temperature of an individual varies depending on the physiological conditions. Reports on magnetic and copper NPs have shown that change in temperature can control both the pattern and quantity of corona formation respectively.…”
Section: Protein Corona Upon Varying the Concentration And Compositiomentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown enthalpy-driven binding of bovine serum albumin (BSA) to QDs, wherein at high temperature the BSA binding was lowered. 51 The normal body temperature of an individual varies depending on the physiological conditions. Reports on magnetic and copper NPs have shown that change in temperature can control both the pattern and quantity of corona formation respectively.…”
Section: Protein Corona Upon Varying the Concentration And Compositiomentioning
confidence: 99%
“…The weaker binding was observed due to an increase in repulsive forces at a lower pH, whereas at pH-9, due to loss in rigidity and tertiary contact, BSA acquired a more exible conformation which in turn led to stronger interactions. 51 Different pH inside the cell (lysosomal-5.3; endosomal-4.6) can trigger similar reactions wherein, the conformational stability and biological activity of the coronated proteins may be altered. 16 Another factor, such as shear stress imparted by the blood in the blood vessels, has also been reported to alter corona formation on PEGylated-liposomes.…”
Section: Protein Corona Upon Varying the Concentration And Compositiomentioning
confidence: 99%
“…Our main object of the studies was core-shell (cadmium selenide and zinc sulfide, respectively) quantum dot nanoparticles, synthesized and exploited industrially mainly due to their quantum state-related optical and electronic properties. Their physico-chemical characteristics which were most relevant to our study are their relatively small size (average diameter 6.2 nm), allowing for their potentially efficient cellular uptake both by triggered endocytosis and more passively by macropinocytosis [ 22 , 23 ]; poly-anionic carboxyl group surface modification, providing potential mechanisms of escape to cytoplasm [ 24 ]; and adsorptive interactions with important cellular components, including proteins [ 25 ] and mitochondrial lipids [ 26 ]; and the inclusion of two heavy metal elements in their structure, cadmium (in the core) and zinc (in the shell), which both have a plethora of known toxicological effects when in the form of free ions [ 27 ]. These QDs have a broad technological and biotechnological application range, extensively reviewed in [ 28 ], encompassing transistor and semiconductor nanoelectronics fabrication, production of lasers, solar cells and light-emitting diodes, medical imaging, and drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The samples obtained from humans of varying ages, sex, diets, states of health and inter-individual variabilities have an influence on PC. [6,50]…”
Section: Impact Of Pc On the Identity Of Nps In The Biological Milieumentioning
confidence: 99%